Model Surgical Training: Skills Acquisition in Fetoscopic Laser Photocoagulation of Monochorionic Diamniotic Twin Placenta Using Realistic Simulators - Wataganara, Tuangsit (J Vis Exp, 2018)
Fetoscopic laser coagulation of arterio-venous anastomoses (AVA) in a monochorionic placenta is the standard of care for twin-twin transfusion syndrome (TTTS), but is technically challenging and can lead to significant complications. Acquiring and maintaining the necessary surgical skills require consistent practice, a critical caseload, and time. Training on realistic surgical simulators can potentially shorten this steep learning curve and enables several proceduralists to acquire procedure-specific skills simultaneously. Here we describe realistic simulators designed to allow the user familiarity with the equipment and specific steps required in the surgical treatment of TTTS, including fetoscopic handling, approaches to anterior and posterior placenta, recognition of anastomoses, and efficient coagulation of vessels. We describe the skills that are especially important in conducting placental laser coagulation that the surgeon can practice on the model and apply in a clinical case. These models can be adapted easily depending on the availability of materials and require standard fetoscopy equipment. Such training systems are complementary to traditional surgical apprenticeships and can be useful aids for fetal medicine units that provide this clinical service.